Canthaxanthin Retinopathy with Visual Loss: A Case Report and Review - Robert A. Beaulieu; Ronald E. Warwar; Bruce M. Buerk (Case Reports in Ophthalmological Medicine)
Canthaxanthin is a naturally occurring chemical, which is most commonly utilized as a colorant for food and dyes or a skin bronzing agent. Its most prevalent impact on human health is canthaxanthin retinopathy, which appears as birefringent, yellow to red crystals surrounding the macula. This occurs with increasing, dose-dependent exposure. Generally, patients remain asymptomatic and findings may only be evident on funduscopic examination. Cessation of canthaxanthin ingestion appears to reverse the retinopathy, but the time until crystal disappearance is variable. Despite a usually favorable outcome, long-standing visual changes may occur. We report a case of an 84-year-old woman with significant visual loss secondary to canthaxanthin retinopathy that ultimately improved upon cessation of the drug.